ANALISIS BIAYA OPERASIONAL TERHADAP KINERJA KEUANGAN PADA PT. BANK NEGARA INDONESIA (Persero) Tbk CABANG MAKASSAR - Hj. Nuraini Rasyid (AkMen JURNAL ILMIAH, 2013)
This study aims to 1), to determine whether the company's operating costs have been managed effectively, 2), to determine the factors that affect the cost of operating what the company's financial performance. From the research menunjukkanBiaya-costs incurred by the company during the last three years tends to increase with the increasing amount of its assets, while net income generated in 2012 a decline, in 2011 the company generated earnings power has increased, and in 2012 re-experiencing decline. The decline was due to the greater percentage decline than the percentage decrease in NPM ATO companies, Year 2011 Net Profit Margin increased to 31.65%. In 2012 NPM decreased derastis obtained from the previous year. This is due to the net operating income fell derastisnya as a result of the increase in operating expenses, in 2010 each dollar of assets the company can generate interest income of Rp. 0.0556. Then in 2011 increased to Rp. 0.0715. For the year 2012 dropped to only Rp. 0.0625. The decline was due to lower revenues while increasing the amount of assets